Development of Scrapbook Learning Media in Basic Culinary Subjects at SMK Negeri 3 Padang - Wajdi, Farelina; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research is motivated by the use of an merdeka curriculum which gives schools and teachers the authority to carry out learning using practicums or not, as well as variations in learning media which are still lacking in Culinary Basics subjects which have an influence on student learning outcomes. The aim of this research is to analyze the validity of Scrapbook learning media and the practicality of Scrapbook learning media during the learning process. This type of research is research and development (RnD). The product trial subjects were lecturers on learning media and basic culinary arts, teachers of basic culinary subjects and X Culinary students at SMK Negeri 3 Padang. The research data analysis technique is the Aiken's V formula and the practicality value is analyzed descriptively. The research results obtained were validation of media development by media and material experts of 0.77 which was declared valid and 0.89 which was declared very valid. The practicality of using Scrapbook learning media by basic culinary subject teachers and Culinary X students is 90% with very practical criteria.